Spirituality and mental health – investigating the association between spiritual attitudes and psychosomatic treatment outcomes - Hinterberger, Thilo; Walter, Nike (Frontiers in Psychiatry, 2025)
BackgroundThe relationship between spirituality and mental health has garnered attention, fostering overall well-being. Spirituality, posited as a protective factor, may enhance resilience and provide meaning, thus benefiting mental health. This study aims to identify spirituality-associated factors influencing clinical outcomes in psychosomatic inpatients and validate the Transpersonal Spirituality Inventory (TSI).MethodsThe study involved 4952 psychosomatic inpatients completing the Transpersonales Vertrauen (TPV) and 7739 patients completing the TSI, with assessments conducted at admission and discharge. Additional instruments included the ISR for symptom rating and the LK-18 for life skills. Factor analysis and Spearman’s rank correlation were used to evaluate the validity of TSI and the relationship between spirituality and clinical outcomes.ResultsFactor analysis confirmed the TSI’s two-factor structure: “centered connectedness” (F1) and “transcendent orientation” (F2), with satisfactory internal consistency (Cronbach’s α = 0.824 for F1 and 0.644 for F2). Higher spirituality levels, particularly in transpersonal trust and centered connectedness, correlated with lower depression and psychosomatic symptoms (ISR). Although these correlations were generally weak, significant associations were found between spirituality and life competences, particularly in meaning, belief, and values (r = .595 for TPV and .598 for TSI F1).ConclusionDespite correlations between psychosomatic health and spirituality as measured with TPV and TSI were rather small several spirituality items could be identified which seem to have a prominent connection to the diagnosis and development of psychosomatic health. Specific spiritual attitudes, such as access to inner stillness and connection to a greater whole, were linked to positive treatment responses and reduced symptom burden. These findings suggest potential benefits in incorporating spirituality into psychosomatic treatments, though its complex and multifaceted nature warrants further investigation.